Celebrity Politics: The Politics of the Late Modernity? - Marsh, David; 't Hart, Paul; Tindall, Karen (Political studies review, 2010)
The academic literature on celebrity politics is rarely systematic; more often it is superficial and anecdotal. In addition, most of the literature focuses either upon classifying different types/categories of celebrity politicians and their roles in politics, or upon the question of whether the growth of celebrity politics undermines or enhances democracy. In this article we consider both of these issues more systematically and, in doing so, work towards a more coherent understanding of the mechanisms that influence modern governance and the operation of contemporary democracy.